Mobile application with travel guidance for shuttle bus users in NTU - Chan, Alfred Choon Kiat (Nanyang Technological University, 2020)
The purpose of the project was to create an application that assist users to travel around NTU. Mode of traveling will be a mixture of NTU shuttle bus and walking. By inputting both the current location (Manually or by GPS) and the destination, the application will display useful information and guide the user to the destination. In addition to the guidance, the application will inform the user if they were about to reach the bus stop that they will need to alight at. The application uses an algorithm to compute and return multiple routes for the user to choose to reach the destination. If the user is not following the suggested route, the user will be given a choice of planning the route again from his/her current location to the destination. The list of suggested routes can be further sorted according to the user preferences. User will also be able to search for specified location within NTU and the arrival time of each shuttle bus at each bus stop will be displayed if requested. To summarize, I was given the opportunity to work on this project and hope that the application that was created will be able to assist and give greater conveniences to students or other users who are interested in coming to NTU.